Pengaruh Price Perception, Store Atmosphere dan Product Diversity terhadap Purchase Decision Produk Starbucks Coffee - Hafizh Fitrianna (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of price perception, store atmosphere and product diversity variables on purchasing decisions for Starbucks Coffee products in Yogyakarta. The type of research used is quantitative research. The population in this study were Starbucks Coffee consumers in Yogyakarta. The sampling technique used purposive sampling method with a total sample of 180 people. Data collection techniques using online questionnaires that have been tested for validity and reliability. Multiple regression technique is used as a method of data analysis in answering the hypothesis. The results of this study indicate that: (1) price perception has a positive effect on purchase decisions, as evidenced by a significance value of 0.000 <0.05, and a regression coefficient of 0.715; (2) product diversity has a positive effect on purchase decisions, as evidenced by a significance value of 0.000 <0.05 and a regression coefficient of 0.402; (3) store atmosphere has a positive effect on purchase decisions, as evidenced by a significance value of 0.003 <0.05; and a regression coefficient of 0.243; and (4) price perception, store atmosphere and product diversity have a simultaneous effect on purchase decisions, as evidenced by the calculated F value of 56,290 with a significance of 0.000 <0.05.